Droht eine Immobilienpreisblase in Deutschland? - Philipp an de Meulen; Martin Micheli (Wirtschaftsdienst, 2013)
Nach Angaben der Deutschen Bundesbank sind die Immobilienpreise in den Jahren 2011 und 2012 jeweils um über 5% gestiegen. Nicht zuletzt aufgrund der dramatischen gesamtwirtschaftlichen Folgen der Immobilienpreisblasen in den USA und in Spanien stellt sich die Frage, ob auch in Deutschland eine Immobilienpreisblase droht. Dies untersuchen die Autoren anhand verschiedener Indikatoren für unterschiedliche Segmente des Immobilienmarkts auf regionaler Ebene und kommen zu dem Ergebnis, dass der Preisauftrieb in Deutschland weitgehend auf fundamentale Ursachen und nicht auf eine Blasenbildung zurückzuführen ist. – – Since 2009, real estate prices in Germany have been rising rapidly after a period of stagnation during the Great Recession. This raises the question of whether the recent price increases are fundamentally driven or rather an indication of a real estate bubble in Germany. To tackle this question, we take a look at several real estate demand-side indicators. As real estate bubbles sometimes form in certain sub-segments of the real estate market only, the authors also conduct a disaggregate analysis by looking at different real estate types in Germany's most important metropolitan areas. In what follows, we investigate the relation of real estate prices and rents and test for explosive behaviour of the price-generating processes. Our findings suggest that the recent upswing in the German real estate market seems to be based on fundamental factors. Except for the sub-segment of flats in some of the metropolitan areas, there is no evidence for price increases being unsustainable.
Keywords: C22; R30; R32; 330